Socio-Ecological Vulnerability Assessment and the Resulting in Spatial Pattern: A Case Study of Semarang City - Visilya Faniza; Wisnu Pradoto (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2019)
The aim of this paper is to examine the socio-ecological vulnerability and the resulting in spatial pattern on a city scale. The assessment methods for vulnerability-resilience in the social and ecological have been broadly examined, such as the Environmental Vulnerability Index (EVI) and disaster risk assessment by the BNPB (Badan Penanggulangan Bencana Nasional). However, in some cases, these methods are suitable only in disastrous vulnerability and on a larger scale. The assessment method of socio-ecological systems in this paper has been modified to a city-scale and per the data availability. By using spatial data, this paper analyses the connection between vulnerability-resilience of socio-ecological systems and land coverage pattern. Based on the case study, the finding shows that almost 28% of Semarang city areas are socio-ecologically vulnerable. Mostof the land use of the vulnerable areas is currently used for urban built-up area and agriculture. For future research, this method can be used for vulnerability assessment of the socio-ecological system in other cities and as a consideration for decision making in spatial planning.